2020
DOI: 10.1016/j.nmni.2020.100709
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of chloroquine derivatives in COVID-19 infection: comparative meta-analysis between the big data and the real world

Abstract: In the context of the current coronavirus disease 2019 (COVID-19) pandemic, we conducted a meta-analysis on the effects of chloroquine derivatives in patients, based on unpublished and published reports available publicly on the internet as of 27 May 2020. The keywords ‘hydroxychloroquine’, ‘chloroquine’, ‘coronavirus’, ‘COVID-19’ and ‘SARS-Cov-2’ were used in the PubMed, Google Scholar and Google search engines without any restrictions as to date or language. Twenty studies were identified involving 105 040 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 33 publications
2
64
0
6
Order By: Relevance
“…Finally, two more RCTs have reported no association between HCQ and virological clearance [39] or prevention of disease in individuals exposed to it [40]. A number of factors could explain the difference between our results and the ones observed in these studies [32][33][34][35][36][37][38][39][40] including the following: the clinical-epidemiological design of our work; [30] the involvement of all patients admitted with COVID-19, regardless their past medical history, the time between onset of symptoms and the start of treatment, the duration of admission, and the need for oxygen; the different statistical approach; and the observation in our work of patients from private hospitals, who are likely to have a high socioeconomic status [41]. The safety of the HCQ has been questioned, as it could negatively impact the immune response to the virus, or cause abnormalities in the ECG [33,42,43].…”
Section: Discussionmentioning
confidence: 81%
“…Finally, two more RCTs have reported no association between HCQ and virological clearance [39] or prevention of disease in individuals exposed to it [40]. A number of factors could explain the difference between our results and the ones observed in these studies [32][33][34][35][36][37][38][39][40] including the following: the clinical-epidemiological design of our work; [30] the involvement of all patients admitted with COVID-19, regardless their past medical history, the time between onset of symptoms and the start of treatment, the duration of admission, and the need for oxygen; the different statistical approach; and the observation in our work of patients from private hospitals, who are likely to have a high socioeconomic status [41]. The safety of the HCQ has been questioned, as it could negatively impact the immune response to the virus, or cause abnormalities in the ECG [33,42,43].…”
Section: Discussionmentioning
confidence: 81%
“…Other studies have reported no positive effects [100]. One meta-analysis of publicly available clinical reports suggests that chloroquine derivatives are effective in reducing mortality by a factor of 3 in patients infected with COVID-19 [101]. Few studies, however, have looked at CNS effects.…”
Section: Summary and Perspectives For Future Developmentmentioning
confidence: 99%
“…Pour une crédibilité scientifique des conclusions sur le fondement ou non d'une hypothèse donnée, l'existence de patients sous traitement « placebo » figure parmi les prérequis méthodologiques lors d'un test clinique. Tel a été le cas du test sur l'hydrochloroquine (HCQ), une molécule considérée efficace pour traiter la Covid-19 (Million et al, 2020 ;Lagieret al, 2020), qui, après comparaison statistique entre les résultats obtenus auprès d'un groupe sous placebo et d'un autre traité avec de l'HCQ, s'est avérée non concluant, voire médicalement dangereuse (Horby & Mandray, 2020 ;Boulware et al, 2020 ;Skipper et al, 2020 ;Hoffmann et al, 2020 ;Maisonnasse et al, 2020 ;Cavalcanti et al, 2020). Fioletet al (2020) viennent même de démontrer dans leur méta-analyse que prendre de l'hydroxychloroquine contre la Covid-19 ne sert à rien, et que l'association HCQ -azithromycine augmenterait le risque de mourir.…”
Section: Effet Placebo Et Placebounclassified